الخوف من السعادة والأمن النفسي لدى الشباب الجامعي - مصطفى, يوسف حمە صالح; خان, هەناو حسن محمد (Sulaimani Journal for Humanities, 2018)
The sense of fear of happiness is a fundamental problem, which has negative effects on the personality of the individual and his sense of psychological security, Psychological security is one of the basic conditions upon which the psychological and social compatibility of human beings depends. The current research dealt with an important slice of the society, namely; university youth, who represents an effective components in the society and in its future advancement. The current research aims to identify the level of fear of happiness and psychological security as a whole and by sex and specialization (science_humanity) and the relationship between them in the sample of the study, which included (600) students. It was chosen by random sample method in three universities in kurdistan region (Sulaymaniyah, Arbil and Dohuk). In order to achieve the objectives, two measures were prepared to measure both the fear of happiness and psychological security. The validity of the SPSS was verified after the final application of the measurements on the sample and the data was processed statistically. The results showed that the fear of happiness among university students is at a low level, and they enjoy a degree of psychological security, and there are no significant differences in the level of fear of happiness and psychological security between male and female students. There are significant differences in the level of fear of Happiness between students of both scientific and humanity studies , which is higher among students of humanity studies, and there are no significant differences in the level of psychological security between students of scientific and humanity studies, which is higher among students of scientific studies.